2021
DOI: 10.1002/alz.12245
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral amyloid‐β load is associated with neurodegeneration and gliosis: Mediation by p‐tau and interactions with risk factors early in the Alzheimer'scontinuum

Abstract: Introduction The association between cerebral amyloid‐β accumulation and downstream CSF biomarkers is not fully understood, particularly in asymptomatic stages. Methods In 318 cognitively unimpaired participants, we assessed the association between amyloid‐β PET (Centiloid), and cerebrospinal fluid (CSF) biomarkers of several pathophysiological pathways. Interactions by Alzheimer's disease risk factors (age, sex and APOE‐ε4), and the mediation effect of tau and neurodegeneration were also investigated. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
(82 reference statements)
0
18
0
Order By: Relevance
“…Glial activation is one of the early mechanisms altered in Alzheimer's disease (AD), probably in response to amyloid-β (Aβ) deposition [1][2][3][4][5]. Contrary to what was previously thought, glial activation has emerged as an active contributor to AD evolution [6], which may influence not only the propagation of the main pathological hallmarks but also the clinical evolution of cognitive disturbances in patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Glial activation is one of the early mechanisms altered in Alzheimer's disease (AD), probably in response to amyloid-β (Aβ) deposition [1][2][3][4][5]. Contrary to what was previously thought, glial activation has emerged as an active contributor to AD evolution [6], which may influence not only the propagation of the main pathological hallmarks but also the clinical evolution of cognitive disturbances in patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“… 2 In a follow-up work, we reported that these markers were also associated with cerebral Aβ deposition as measured by PET. 3 However, the relationship between these CSF biomarkers and structural and metabolic alterations in the brain are not well understood, especially in these early phases of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in investigating glial activation markers and their relationship with disease progression, as it has been suggested that inflammatory processes may have an active role in AD [4]. Previous studies proposed that some glial activation markers could be related to disease progression [7,8]. For instance, higher levels of sTREM2, a microglial activation marker [39], have been related to slower rates of Aβ accumulation and disease progression [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…However, until recently, these biomarkers had to be measured in different platforms and using sophisticated methods, which reduced its applicability to clinical practice. Previous studies using this panel have shown alterations in some of these biomarkers in different stages and in relation to different aspects of the disease [7][8][9][10]. However, their clinical utility for predicting disease progression after accounting for core ADbiomarkers is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%